Factors influencing men's involvement in antenatal care services: a cross-sectional study in a low resource setting, Central Tanzania - Nyasiro S. Gibore; Theodora A. L. Bali; Stephen M. Kibusi (BMC, 2019)
Abstract Background Men's involvement can impact the delays in the decision to seek health care and in reaching a health facility, which are contributing causes for increased maternal mortality. Despite of the call to involve men in antenatal care, their participation is not well understood. This study aimed to determine the level of men's involvement in antenatal care and the factors influencing their involvement in these services. Methods A cross sectional study of 966 randomly selected men aged 18 years or older was conducted in Dodoma Region, from June 2014 to November 2015. Face to face interviews were conducted using a pretested structured questionnaire. The outcome variable was men's involvement and was constructed from four dichotomized items which were scored zero to two for low involvement and three to four for high involvement. A multiple logistic model was used to measure the factors influencing men's involvement in antenatal care services. Results The level of men's involvement in antenatal care was high (53.9%). Majority 89% of respondents made joint decisions on seeking antenatal care. More than half (63.4%) of respondents accompanied their partners to the antenatal clinic at least once. Less than a quarter (23.5%) of men was able to discuss issues related to pregnancy with their partner's health care providers. About 77.3% of respondents provided physical support to their partners during the antenatal period. Factors influencing men's involvement in antenatal care were occupation (AOR = 0.692, 95% CI = 0.511-0.936), ethnicity (AOR = 1.495, 95% CI = 1.066-2.097), religion (AOR = 1.826, 95% CI = 1.245-2.677), waiting time (AOR = 1.444, 95% CI = 1.094-1.906), information regarding men's involvement in antenatal care (AOR = 3.077, 95% CI = 2.076-4.562) and men's perception about theattitude of health care providers (AOR = 1.548, 95%CI = 1.090-2.199). Conclusion Overall, more than half of respondents reported high involvement in antenatal care services. Access to information on men's involvement, religion, occupation, ethnicity, waiting time and men's perception about the attitude of care providers were significant factors influencing men's involvement in antenatal care services in this study. Health promotion is needed to empower men with essential information for meaningful involvement in antenatal care services.